User Responsive Automatic Method for Real Time Depression Detection Using Deep Neural Network - Acharya, Jiger Prakashchandra; Shah, Dr.MilindS. (Journal of Neonatal Surgery, 2025)
During last one decade the mental health is becoming a major concerning issue to society as number of various socio-economical, personnel and societal issues related to mental health are increased in exponential manner. Depression is mood disorders which result in severe disabling conditions which affect person’s ability to cope with routine life and real-life challenges which are dynamic in nature. It may occur when person remain more than two weeks in negative state of mind continuously. Depression has observable behavioral symptoms related to affective and psychomotor domains which can be identified. Classical approaches majorly depend on person’s behavioral analysis and family observations during clinical interviews, which are effective if it can be precisely defined and assessed but persons have tendency to conceal it so they are less effective while proposed method with Deep Learning techniques perform the said task with accuracy of 79% and open a new era for health care domain.